Epistemological access in flood-prone primary schools of Western Kenya - Erima, Gloria (My University, 2017)
This doctoral thesis investigates a fairly under-researched area on Equitable Epistemological Access (EEA) in flood-prone schools in the Budalang’i division of western Kenya. Though the meaning of Epistemological Access (EA) is still lacking in literature, for the purposes of this study it may be conceptualised as the access to quality education, denoting the intention to move beyond the physical or formal access to knowledge attainment. The study investigates how schools in this area promote EA, the challenges they encounter and how the schools commit to delivering a socially-just educational experience and comparable learning outcomes to learners. The research was centrally aimed at exploring the conditions which militate against the achievement of EA in flood-prone areas of Western Kenya, where schools confront serious challenges in delivering access to education to learners. This research objective was driven by three sub-questions, investigating how flood-prone schools promote physical and EA for learners; and in what ways different school communities perceived strategies to be effective in promoting EA. Theoretically, the thesis offers a critical examination of the impact of recurring floods on knowledge attainment, progression, persistence and the quality of learner outcomes. Based on Bhaskar’s critical realism philosophy, and within the premises of Sen’s ‘capability approach’ and Nancy Fraser’s social justice theoretical frameworks, the thesis sets out an approach for an understanding of EA and the role education plays in developing individual capacities. The study utilises a convergent mixed methodological approach, based on twenty-three in-depth interviews, a questionnaire and focus group discussions (FGDs). Fifteen of these interviews were with parents and senior school managers at the level of principal and senior teachers from five flood-prone primary schools. Eight other interviews were conducted with representatives of the Sub-county education office, public health, disaster management and the county government departments. The questionnaire survey was completed by a total of 191 Standard Eight pupils from the five primary schools, in addition to FGDs consisting of ten pupils from each of the five schools. The study confirmed nine core indicators that provide the essential rationale for EA: time-on-task, resources, teacher motivation, pedagogy, instructional leadership, parental involvement, school communities, the community/environment and culture. Later in the analysis these are categorised into three factors: i) teacher-mediated, ii) school-mediated and iii) community-mediated. Though data seems to strongly indicate that school resources and teacher motivation are necessary variables that influence learner time-on-task to achieve epistemological access, a further analysis portrays schools as implementing EA indicators only at the physical access level. Beyond these direct findings, the study identified two critical contributions to the discussion around EA in flood-prone schools in western Kenya: the First Generation Factors (FGF) model, which situates the physical access kinds of strategies schools seem to be engaged with already; and the Second Generation Factors (SGF) model, which seems to point to moving towards increasing EA. These two models may be useful when developing policy around (equitable) EA, based on bringing synergies between teachers, the schools and the communities.
A thesis submitted to the Wits School of Education Faculty of Humanities University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, October 2017
Keywords: Educational change--Kenya; Democracy and education--Kenya